Delineation of sulphur deficiencies in Trans-Gangetic Plain and on-farm sulphur management for higher productivity and profits in rice (Oryza sativa)-wheat (Triticum aestivum) system - SINGH, V K; KUMAR, V (The Indian Journal of Agricultural Sciences, 2026)
In the view of assessing the extent of S deficiency in rice (Oryza sativa L.)-wheat (Triticum aestivum L.) growing areas of Trans- Gangetic Plain (TGP) zone and to measure the S response of rice-wheat system on farmers’ field, 1191 soil samples were collected from Rai and Bapoli Agricultural Development Blocks (ADBs) of Sonipat and Panipat districts. The soil samples (0-15 cm soil profile) were analyzed for soil OC and available S content indicated that more than 60% soils were low in OC content and occurrence of S deficiency was also associated with soil OC content. Farmers’ fertilizer management practices were highly imbalanced and skewed towards N and use of S fertilizers was generally negligible (only 17% farmers’ apply). On-farm trials conducted on S deficient soils during 2004 to 2007 with four levels of S (0, 15, 30 and 45 kg S/ha) in a randomized block design indicated that S applied at 30 to 45 tonnes/ha, increased rice yields significantly (1.12 to 1.17 tonnes/ha and 1.26 to 1.35 tonnes/ha, respectively) compared with no-S application. Succeeding wheat also showed significant response to residual S at 30 or 45 kg S/ha. Compared with control, total S intake at 45 kg S/ha was higher by 129% to 154% in rice and 86% to 81% in wheat. Lower S application dose (15 kg/ha) did not leave residual effect on the succeeding wheat crop. Skipping S application caused depletion in available S content of the soils (23 to 42%) over initial S status. After 03-crop cycles, apparent S balance was positive at both the study sites when rice received more than 30 kg/ha S. Substantial yield gains and higher value cost ratio due to S fertilization (Rupees 95 to 103 /Re invested in S) was further substantiated with impact studies conducted during 2007 which reveal that more than 33% farmers started using S in fertilization schedule for rice-wheat system.